Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Sum of infinite series....?
Sorry, it's been a while since I've done this...
The series is [(2/5)^n][(3/5)^(n-1)]
How do I find this sum? I can't just find each series separately and multiply them, can I?
Sorry...n does start from 1.
3 Answers
- sahsjingLv 71 decade agoFavorite Answer
If n starts from 1, then the sum is (2/5)/[1-(6/25)] = 10/19
---------
Ideas to get r: r = [(2/5)^(n+1)][(3/5)^(n)] / [(2/5)^n][(3/5)^(n-1)] = (2/5)(3/5) = 6/25
- Randy PLv 71 decade ago
It can be written as a geometric series, a sum of terms of the form a*r^n.
[(2/5)^n][(3/5)^(n-1)] = (2/5)^n (3/5)^n (3/5)^-1
= (6/25)^n * (5/3) so a = 5/3 and r = 6/25
You didn't say what your starting term was, but the sum of a*r^n for n = 1, 2, ... is a*r/(1 - r).
The sum from n = 0 to infinity is a/(1 - r).
- nleLv 71 decade ago
I assume you find the sum from n= 1 to infinity.
No, you cannot find the sum of each series and multiply them.
Your series is of the form a^n * [ b^ (n-1) ] = a^n * ( b^n /b ) = [ (ab)^n /b ]
So use the formula of the geometric series.